2022
DOI: 10.1093/trstmh/trac002
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of intestinal helminths in humans and animals in the Philippines

Abstract: Background A large number of studies have assessed risk factors for infection with soil-transmitted helminths (STH), but few have investigated the interactions between the different parasites or compared these between host species across hosts. Here, we assessed the associations between Ascaris, Trichuris, hookworm, strongyle and Toxocara infections in the Philippines in human and animal hosts. Methods Faecal samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…The interaction between different parasite populations (within and between hosts) and host populations, rather than associations play a significant role 17 . Though the specifics of these interactions within the host are unknown, some are sought to be synergistic where the presence of one parasite may encourage the occurrence of future parasitic infections, while others are thought to be antagonistic where parasites compete for the same ecological niche within the host 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between different parasite populations (within and between hosts) and host populations, rather than associations play a significant role 17 . Though the specifics of these interactions within the host are unknown, some are sought to be synergistic where the presence of one parasite may encourage the occurrence of future parasitic infections, while others are thought to be antagonistic where parasites compete for the same ecological niche within the host 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Human factors such as age may influence the pathogenesis of disease caused by STH infection (high Ascaris , Trichuris , and Toxocara worm loads lead to more severe illnesses in children) (Else et al 2020 ). Aside from coevolution, greater human occupancy in animal habitats and close contact or affiliation with pets and domestic animals in human dwellings, augmented by individual variables and behaviors, allow for zoonotic pathogen exposure (Kajero et al 2022 ; WHO 2020 ). Pet ownership is increasing in many households, and too close contact or association can be harmful to pet owners (Kamani et al 2021 ), particularly in areas where the owners are unaware of the associated zoonotic disease risks and thus do not take the necessary precautions to avoid any potential health hazards (Moro and Abah 2019 ).…”
Section: The Concept Of One-healthmentioning
confidence: 99%
“…A recent study has reported that there is a balanced association between A. lumbricoides, trichuris trichiura and (ancylostoma duodenale, necator americanus) infections in humans. However, the study did not account for the age group studied [16].…”
Section: Introductionmentioning
confidence: 99%